Dinosaurs come alive at the youth floor - Mahdi, Rasidah (Universiti Teknologi MARA, Sarawak, 2004)
Pewani UiTM Sarawak Campus organized an art competition on 11 June 2004. The one morning session attracted about 30 aspiring artists. They were put into two separate age groups. The younger group were putting colors to the dinosaur pictures given to them while the other group tried to come up with personalized cards which were mainly for the Fathers’ Day celebration. The activities provided an opportunity for the children to interact and express themselves through colors and work of art.